Financial instruments and equity structures for raising capital in co-operatives. Issue 1 (7th March 2016) - Mamouni Limnios, Elena Alexandra; Watson, John; Mazzarol, Tim; Soutar, Geoffrey N.
Abstract : Purpose: – A key issue faced by co-operative enterprises is how to raise external equity capital without compromising member control. The purpose of this study is to examine the potential of a special type of financial instrument called a Cooperative Capital Unit (CCU) introduced into the Australian legislation to facilitate external investment while maintaining member control. Design/methodology/approach: – A Delphi panel and six focus groups were used to provide an understanding of the challenges associated with cooperative governance and financing and to aid the development of a conceptual framework for the implementation of CCUs. Findings: – The findings from these Delphi panel and six focus groups were used to develop a proposed framework that the authors believe will be useful in structuring equity-like instruments depending on the purposes they might serve. In particular, the authors propose a new form of cooperative ownership and equity structure that could: better align member and investor interests; provide a mechanism to strengthen one role over the other depending on the needs of the cooperative; and provide investors with a better sense of security while retaining member control. Originality/value: – To the best of the authors' knowledge, the cooperative ownership and equity structure proposed in this study are novel and not currently found in theory or practice. The insights provided by this study should, therefore, be of interest to a wide range of stakeholders, including cooperatives; professional advisors to these businesses; government regulators; investors; and researchers.